Violations Of Police Ethics And Morality In Pontianak Polresta - Riwayati, Anny; Handayani , Dwi Nur (PT. Riset Press International, 2024)
Indonesia is a country of law, every offense must have a penalty and is reinforced by the regulations listed in the law. Crime cases in West Kalimantan, especially in Pontianak in 2023, are the second largest case. Of these cases, one of them is from the police. It was unexpected and surprising and many media reported it. One of the duties of the police to maintain the security of the community, on the contrary, makes the community restless and distrustful of the police. This research uses qualitative methods by collecting data from relevant sources. The results of the analysis show that cases of child abuse committed by unscrupulous police officers are behaviors that deviate from the police code of ethics. The ethics built in the police are not optimal in the police because with their authority they can take unethical actions. In restoring police confidence in the hearts of the community, the police carry out activities that are closer to the community and carry out tighter supervision within each police officer The Polresta Party provides penalties that make others not follow in the footsteps of these violations. One suggestion from the researcher is to emphasize faith in each police officer to devote to the state and protect the community.